ECMI resonance in AKR revisited: Hyperbolic resonance, harmonics, and wave–wave interaction - Baumjohann, W.; Treumann, R. A. (Frontiers in Physics, 2023)
Recapitulation of the resonance condition for the fundamental and higher electron cyclotron harmonics in the Electron Cyclotron Maser Instability (ECMI) enables radiation below and confirms the possibility of radiation in a narrow band above harmonics n>1. Near the n=1 resonance on the confined lower X-mode branch, amplification is supported by the decrease of phase and group speeds. Confined slow large-amplitude quasi-electrostatic X-modes nonlinearly modulate the plasma to form cavitons until self-trapped inside them at further increasing wavenumber. They undergo wave-wave interaction, enabling escape to free space in the second harmonic band below n=2. At sufficiently large parallel wavenumber (oblique propagation), the fundamental resonance n=1 is hyperbolic, a possibility so far missed but vital for an effective ECMI in the upward current region. Here, the resonance hyperbola favourably fits the loss cone boundary, the presumably important ECMI upward-current source-electron distribution, to stimulate ECMI growth at available auroral electron energies.